Possible associations of periodontal pathology and new coronavirus infection (COVID-19) - Dmitry I. Trukhan; Anatoly F. Sulimov; Larisa Yu. Trukhan (Клинический разбор в общей медицине, 2022)
The novel coronavirus infection (coVId-19) pandemic, spread by the SArS-coV-2 virus, has become a challenge to healthcare systems around the world. The most vulnerable group, in which the risk of adverse outcomes is especially high, are patients with comorbid pathology. We searched the literature for the period from the beginning of the pandemic until may 25, 2022, devoted to the study of the relationship between periodontal pathology and the new coronavirus infection coVId-19 in the Pubmed and Scopus electronic search engines. The sources found can be divided into 2 groups: 1) theoretical background of a possible association periodontal pathology and coVId-19; 2) clinical observations. The theoretical prerequisites for a possible association include: 1) the comorbidity of periodontitis and its close relationship with the metabolic syndrome, obesity, diabetes mellitus, atherosclerosis, arterial hypertension and other cardiovascular diseases, which are accompanied by an increase in infection, severity of the course, the development of complications, an increase in mortality from infection coVId-19; 2) target cells of the SArS-coV-2 virus in the oral cavity are located in the oral cavity; 3) systemic inflammation in periodontitis has similar features to coVId-19, including a similar cytokine expression profile; 4) the possible role of periodontal / periodontal bacteria in the aggravation of pulmonary infections, including coVId-19. In a number of studies, the theoretical prerequisites for the existence of an association between periodontal pathology and coVId-19 have received clinical confirmation. In conclusion of the review, it is necessary to pay attention to practical recommendations indicating the importance of maintaining periodontal health and the need for proper oral hygiene as one of the important aspects of the prevention and treatment of coVId-19.